Letopis Fakultete za gradbeništvo, prometno inženirstvo in arhitekturo 2022/2023 - Marina Bajić; Pogačar, Kaja; Letnik, Tomislav; Rodošek , Vlasta; Držečnik, Mateja; Ćatović , Almira (2023)
Yearbook Faculty of Civil Engineering, Transportation Engineering and Architecture 2022/2023. The publication provides an overview of the Faculty's achievements in the academic year 2022/23 and briefly presenting the Faculty's activities and study programmes, namely Civil Engineering, Industrial Engineering, Traffic and Transportation Engineering and Architecture. In addition, the best publications, projects, excursions, workshops, exhibitions, international visits as well as the work of the Student Council, the FGPA Alumni Club and the work of the Committe-es and the specialised services are presented. All diploma, master's and doctoral theses of the academic year 2022/23 are included.
Keywords: yearbook; study year 2022/2023; Faculty of Civil Engineering, Transportation Engineering and Architecture; faculties; achievements, projects